Motu ma le taula : taeao afua = Severed from the anchor : a new beginning : the growth of the Congregational Christian Church of Samoa, Wellington : a thesis submitted to Massey University in partial fulfilment of the requirements for the degree of Master of Education (Adult Ed.) - Enari, Sotiaka (Massey University, 2002)
The utmost dread of a Samoan is realising the condition commonly expressed as 'motu ma le taula' (severed from the anchor), or 'motu mai fanua' (detached from the homeland), or 'motu ma le ta'i' (cut-off from the aim or guide). Living abroad, they have to negotiate their migrant situation and manage their double identity. Deterritorialised peoples as a result of migration are always thrown into wider spaces and deep-ends. It amounts to social, political, economic, and symbolic loss. They are forgotten in terms of having no history. Their histories are bound up in national histories. But the deterritorialised have enabling visions within their cultural texts that transform their situations manifested as they strive to define themselves as a people. Self-definition inclines towards rediscovering history for meaning entrenched in heritage. It sets the path for community building that reconstitutes a base in the new space to hold a life of the edge-way. The Congregational Christian Church of Samoa (CCCS), Wellington, defined itself as it grew as a faith community and cultural community. Affective-links played a major part in overcoming contradictions and uncertainties that sprang forth from intercultural encounters and marginal existence. Neither the tolerance nor the domination paradigms have much to offer in understanding the growth of the Wellington CCCS. Rather, this thesis looks at the effort of the community through the process of learning from experience, experience being the conglomerate of memory-scapes of the past and present. The process shows human potential responding to the notion of possible worlds, which enables people to endure negativity, find motivation, and empowers them to modify situations, even reconstructing their identity and culture in their new environment. In the final analysis, the resolve of the people counts above all. The resolve is not just a matter of replenished self-belief, but the community-self that believes.
Keywords: Congregational Christian Church in Samoa; New Zealand; Samoans -- Religion; Congregational churches -- Wellington